BITHIENOLs: Promising C2‐Symmetric Biheteroaromatic Diols for Organic Transformation. Issue 4 (27th January 2017) - Gabrieli, Sara; Cirilli, Roberto; Benincori, Tiziana; Pierini, Marco; Rizzo, Simona; Rossi, Sergio
Abstract : 2, 2′, 5, 5′‐Tetraphenyl‐3, 3′‐bithiophene‐4, 4′‐diol, the first member of a new class of chiral C 2 ‐symmetric atropisomeric diols based on a biheteroaromatic scaffold, has been synthesized. Dynamic enantioselective HPLC experiments revealed a racemization barrier of 22.9 kcal/mol at 25 °C, which is high enough to permit the chromatographic collection of both enantiomers on a semi‐preparative scale, but at the borders of application as a promoter in asymmetric catalysis. The ground and transition states involved in the enantiomerization process have been identified through DFT calculations, which suggest the intermediacy of a tautomeric species in which a thiophen‐3‐ol unit and a 2, 3‐dihydrothiophen‐3‐one ring are present. The proposed racemization mechanism is supported by the results of dynamic HPLC experiments. Calculations also suggested which substituent groups at the 2, 2′‐positions of the thiophene rings could lead to an increase in enantiomerization barriers sufficient to confer full configurational stability on the 3, 3′‐bithiophene framework. Abstract : A new class of chiral C 2 ‐symmetric atropisomeric diols based on a biheteroaromatic scaffold has been synthesized. The ground and transition states involved in their enantiomerization have been identified through DFT calculations, which suggest a tautomeric intermediate in which a thiophen‐3‐ol and a 2, 3‐dihydrothiophen‐3‐one are present. The racemization mechanism is supported by dynamic HPLC.